Effects of sensory integration training on balance function and executive function in children with autism spectrum disorder: evidence from Footscan and fNIRS - Deng, Junchen; Lei, Ting; Du, Xiru (Frontiers in Psychology, 2023)
This investigation delves into the effects of Sensory Integration Training (SIT) on the balance and executive function in children with autism spectrum disorder (ASD). We employed Footscan to gather biomechanical evidence and functional Near-Infrared Spectroscopy (fNIRS) to monitor neural activation. Our study comprised two participant groups: the control group (n = 9) and the experimental group (n = 9). Both groups participated in balance assessments using the Sharpened Romberg Test (SRT) under varied visual conditions and completed the Go/No-Go task to gauge executive function. Results indicate that the SIT intervention significantly improved the balance function in children with ASD, particularly in Visual Deprivation (VD) scenarios. Further, neurophysiological measurements from fNIRS pointed to increased activation levels in the right Inferior Frontal Gyrus (R-IFG) and right Middle Frontal Gyrus (R-MFG), implying a notable improvement in executive function. By synthesizing behavioral data with neurophysiological findings, we discerned the potential of R-IFG/MFG activation to serve as a reliable biomarker for assessing executive function in children with ASD. Overall, our findings accentuate the efficacy of SIT in ameliorating balance and executive functions and underscore its potential in effectively organizing and processing sensory information in the brain. While our study has its limitations, it offers invaluable insights into intervention methods for ASD, paving the way for refined experimental designs and more tailored intervention strategies in the future.